Re-diagnosed and Re-treated Orofacial Granulomatosis: A Case Report - Ahamed Ismail Samu Fathima; Sarumathi Thirugnanamurthy; Guruswathy Ravikumar; Kavitha Mathivanan (Wolters Kluwer Medknow Publications, 2024)
Orofacial granulomatosis is an uncommon skin condition affecting the face and predominantly the lips, also referred to as cheilitis granulomatosa. We will be discussing a case of a 50-year-old female with a history of swollen lips for the past 3 years who had visited various hospitals and also had undergone multiple diagnostic tests with no conclusive diagnosis and was treated for the possible diagnoses of hemangioma and arterio-venous malformation with ineffective treatment results. Upon careful elicitation of details, we arrived at the diagnosis of orofacial granulomatosis and treated her with a combination therapy with resultant rapid regression of the lesion.